Uji in Vitro Penghambatan Aktivitas Escherichia coli dengan Tepung Cacing Tanah (Lumbricus rubellus) - H Julendra; A Sofyan (Media Peternakan, 2007)
This research was conducted to study the inhibition growth of E. coli by using earthworm (Lumbricus rubellus) meal. The earthworm meal was used in various concentrations, i.e. 0, 25, 50, 75 and 100 mg of earthworm meal in 100 ml DMSO for 0%, 25%, 50%, 75% and 100% (w/v) as treatments respectively. Data were analyzed by ANOVA in Randomized Complete Block Design. Duncan's multiple range test and polynomials orthogonal were used. Inhibition effects were measured through agar well diffusion test. Results showed that earthworm meal contain antibacterial compound which inhibit E. coli activity. There was a significant difference (P < 0.05) between earthworm meal treatments and control. The best antimicrobial effect was found in treatment of 50% (w/v) of earthworm meal and significantly higher than those of 25, 75 and 100% (w/v), but 25% (w/v) was not different (P > 0.05) with 75% (w/v). It is concluded that earthworm meal is capable to inhibit E. coli in-vitro at the optimum level of 50% (w/v). Key words: earthworm meal, E. coli, in-vitro, agar well diffusion